1996
DOI: 10.1107/s0021889896001628
|View full text |Cite
|
Sign up to set email alerts
|

A New Measurement of Crystal Shapes for Absorption Corrections

Abstract: A new method is described for determining a crystal shape having an arbitrary face. A charge‐coupled device camera and computer graphics were used for the determination. This method is an application of the principle of computerized tomography. In a preliminary estimation for the measurement, an accuracy of better than 2.0% was obtained for crystal shapes having squarish faces. On the other hand, an accuracy of better than 0.6% was obtained for roundish specimens, such as ellipses or spheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Mounting the crystal on the tip of the micropipette allows the detection of shadow projections via a video system. With the method of back projection, the crystal shape and crystal volume can be easily calculated (Kiefersauer et al, 1996;Izumi et al, 1996). The response of the crystal lattice towards humidity changes can be monitored over time by analysing the crystal extension.…”
Section: Optical Analysis Of the Crystalmentioning
confidence: 99%
“…Mounting the crystal on the tip of the micropipette allows the detection of shadow projections via a video system. With the method of back projection, the crystal shape and crystal volume can be easily calculated (Kiefersauer et al, 1996;Izumi et al, 1996). The response of the crystal lattice towards humidity changes can be monitored over time by analysing the crystal extension.…”
Section: Optical Analysis Of the Crystalmentioning
confidence: 99%
“…Unfortunately, the existing practice of preliminary empirical scaling makes the refinement of sample sizes impossible. Prior to the implementation in diffractometer software of programs developed for reconstructing sample shape from photographs (Izumi et al, 1996;Zhurov, 2005;Leal et al, 2008), our method is most effective. In this paper, it has been shown that empirical absorption correction should be applied only at the very end of calculations, when all other corrections with a physical meaning have already been introduced.…”
Section: Tablementioning
confidence: 99%
“…In three dimensions, this leads usually to a volumetric representation in which the object is quantized as a voxel. 2 This type of modelling was implemented for the first time in crystallography by Izumi et al (1996), although the test crystal of V 3 Si had no surrounding support system. In the present work we extend the approach to distinguish between crystal, loop and cryoprotectant components of the mounted sample.…”
Section: Three-dimensional Modelling Of Macromolecular Crystals Cryomentioning
confidence: 99%